Síntese de precursores de ácidos naftênicos do tipo ARN - Bottocim, Ramon Ramires Trancoso (2022)
The process of precipitation of naphthenic acids in petroleum processing is expensive and raises numerous questions about the factors that lead to this. A compound responsible for the precipitation of these acids was identified with a very peculiar characteristic, the compound has a range of 78 to 80 carbon atoms, being a tetra-acid and was called ARN, eagle in Norwegian, because its carbon chain resembles the claws of an eagle. This compound has been used as a model in the study of precipitation and emulsion formation. Other compounds are also used as standard, however, all of them with aromatic chains in their composition, which is not found in the naturally obtained ARN structure. This study aims to synthesize an ARNtype naphthenic acid standard with similar structure to the one known for this kind of compounds, so that it can be used in the subsequent study of precipitation and emulsion formation/stability. For this, the intermediates were synthesized and later will be used to prepare the proposed standard.